2022
DOI: 10.7554/elife.77584
|View full text |Cite
|
Sign up to set email alerts
|

Combining transgenesis with paratransgenesis to fight malaria

Abstract: Malaria is among the deadliest infectious diseases, and Plasmodium, the causative agent, needs to complete a complex development cycle in its vector mosquito for transmission to occur. Two promising strategies to curb transmission are transgenesis, consisting of genetically engineering mosquitoes to express antimalarial effector molecules, and paratransgenesis, consisting of introducing into the mosquito commensal bacteria engineered to express antimalarial effector molecules. Although both approaches restrict… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…S1). The capacity of mosquitoes carrying D. tsuruhatensis TC1 to transmit P. berghei from infected to naïve mice ( 13 ) was also assessed (Fig. 1C).…”
Section: Bacterial Colonization Of the Anopheline Midgut And Inhibiti...mentioning
confidence: 99%
“…S1). The capacity of mosquitoes carrying D. tsuruhatensis TC1 to transmit P. berghei from infected to naïve mice ( 13 ) was also assessed (Fig. 1C).…”
Section: Bacterial Colonization Of the Anopheline Midgut And Inhibiti...mentioning
confidence: 99%
“…Our previous laboratory and field studies revealed that two genetically engineered bacteria, Serratia AS1, and Enterobacter cloacae, are suitable candidates for paratransgenic control of leishmaniasis (14,(24)(25)(26)(27). These bacteria were found in sand flies (12,(28)(29)(30)(31) and genetically manipulated to produce effector molecules that interfered with Leishmania development in the sand fly gut and consequently reduced the chance of parasite transmission (13,14,25,32). Also, these two bacteria were used successfully in the paratransgenesis strategy for combating malaria in laboratory conditions (15,26,33,34).…”
Section: Introductionmentioning
confidence: 99%